Impact of lufenuron on hematology, serum biochemistry, antioxidant enzymes, and histopathology in broiler chickens - Abu Baker Siddique; Riaz Hussain; Zeeshan Ahmad Bhutta; Muhammad Zishan Ahmad; Iahtasham Khan; Sana Alam; Rabbiah Manzoor Malik; Ayaz Mammadov; Farid Shokry Ataya (PLoS ONE, 2025)
The widespread utilization of synthetic chemicals, including weedicides, pesticides, insecticides, and fertilizers, has contaminated the environment. Therefore, it is crucial to recognize the ongoing threat of various stressors, including exposure to synthetic and natural chemicals on various target and non-target living organisms. Lufenuron is extensively utilized in controlling ectoparasites in companion animals and may offer a potential solution for addressing analogous challenges in commercial poultry farming. For this purpose, an experimental study was conducted to estimate the potential toxic effects of lufenuron in chickens. A total of 75 broiler chickens were housed under standard environmental conditions for the period of 39 days following a 7-day acclimatization. Birds were randomly divided into five groups (A-E), each consisting of 15 birds, and administered different doses of lufenuron in groups B-E @ 4, 8, 12, and 16 mg/kg body mass, respectively. Various hematological, biochemical, and histopathological biomarkers were assessed in blood and visceral organs. In the current experimental trial, the values of RBC count, PCV, hemoglobin, and MCHC significantly (<0.05) decreased, while WBCs and MCH significantly (<0.05) increased in treated birds. Results showed significantly increased values of renal function tests (urea and creatinine), liver function tests (ALP, AST, and ALT), and cardiac biomarkers (cholesterol and creatinine kinase) in broilers exposed to higher doses of lufenuron. Various histopathological ailments were examined in the liver, kidneys, and heart of the broiler in the dose and time-dependent manner. The current study showed that lufenuron induces oxidative stress, depletion of various antioxidant enzymes, and histoarchitectural alterations in multiple visceral organs.